Legal Policy On Fulfilling The Right To Clean Water For Indonesian Citizens - Razikin, Razikin (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that the state controls the rights to water resources with the sole purpose of the prosperity of the people. The meaning of Article 33 paragraph (3) philosophically is the embodiment of the 5th Principle of Pancasila, namely Justice for All Indonesian People, where water as one of the national riches is a need of the people which is controlled by the state within the framework of providing justice and prosperity for all Indonesian people. The general regulation of water fulfillment has been explained in Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia which provides a guarantee from the state for the people's right to water, including in this context the right to clean water. This concept is then further explained in Article 6 of Law Number 17 of 2019 concerning Water Resources. However, the SDA Law provides a loophole for water management, no longer solely for the public interest but shifting to private and even commercial interests. Article 8 of the SDA Law as amended by Article 53 of Law Number 11 of 2020 concerning Job Creation regulates the state's priorities for the people's right to water, namely: (a). daily basic needs; (b). people's agriculture and (c). use of Water Resources for business needs to meet daily basic needs through the Drinking Water Supply System. As a result, based on BPS data, 33.4 million Indonesians lack clean water and 99.7 million people lack access to good sanitation facilities. Legal policies on the fulfillment of clean water for Indonesian citizens must be carried out immediately as an anticipation of a medium crisis in 2025, the results of research by the National Water Resources Council. Because if there is no concrete legal policy, such as budget policy, institutional arrangements and changing existing legal products with the concept of the State controlling the rights to water resources with the sole intention of the people's prosperity, otherwise in 2040 Indonesia will be one of the countries experiencing a long water crisis, if that happens then death, poverty and hunger will become a serious problem for the Indonesian nation